2010
DOI: 10.1177/147776061002600102
|View full text |Cite
|
Sign up to set email alerts
|

Paints Based on Waste Expanded Polystyrene

Abstract: A formula for making paint was developed using waste expanded polystyrene foam (EPS) as a binder. This method replaces the alkyd resin in most commercial paint, which is derived from the byproducts of refining crude oil. Experimental results showed that 27% waste polystyrene foam can be incorporated in the paint formulation. Basic performance tests for EPS paint were conducted and evaluated, and the developed formulation was compared with commercial paint containing modified alkyd resin as a binder. Test resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…Expanded polystyrene can replace the conventional binders in emulsion paint such as PVA without altering the properties and performance of such a paint. Myint, Zakaria [69] employed recycled expanded polystyrene waste in paint formulation to replace the conventional alkyd resin that is used in some commercial paints. Their result revealed that 27% of waste polystyrene can be incorporated in paint formulation without altering its basic properties.…”
Section: Expanded Polystyrene As a Binder In Emulsion Paintmentioning
confidence: 99%
“…Expanded polystyrene can replace the conventional binders in emulsion paint such as PVA without altering the properties and performance of such a paint. Myint, Zakaria [69] employed recycled expanded polystyrene waste in paint formulation to replace the conventional alkyd resin that is used in some commercial paints. Their result revealed that 27% of waste polystyrene can be incorporated in paint formulation without altering its basic properties.…”
Section: Expanded Polystyrene As a Binder In Emulsion Paintmentioning
confidence: 99%
“…Several attempts have been made by researchers towards reclaiming EPS into useful products for various applications. Myint, Zakaria, and Ahmed 14 formulated a paint based on an EPS waste binder intending to replace alkyd resin. They reported an optimum performance at 27% EPS incorporation in the paint formulation which was comparable with commercial alkyd resin paint.…”
Section: Introductionmentioning
confidence: 99%
“…EPS used in this study was purchased from S-tech Thermocool Industry, Cherthala, Kerala with a density value of 15 Kg/m 3 . Waste EPS was not selected for the study because of the need to get a clean material for the initial studies.…”
Section: Methodsmentioning
confidence: 99%
“…Owing to its light weight, buoyancy, thermal insulation, dimensional stability, chemical resistance, electrical properties, hygienic appearance, low cost etc., EPS is used for a large number of applications. Today, global consumption of EPS exceeds 3 million tons with an increase of approximately 6% a year [2,3]. After use, EPS usually ends up in landfills or is incinerated.…”
Section: Introductionmentioning
confidence: 99%